Acoustical shadow of a sphere immersed in water. II - FILIPCZYŃSKI, Leszek; KUJAWSKA, Tamara (Archives of Acoustics, 1989)
Assuming a continuous plane wave incident on a rigid sphere immersed in water the authors computed directivity characteristics of the acoustic pressure behind the sphere. The obtained results were converted and presented in the rectangular coordinate system in the form of acoustic isobars for ka values in the range between 4π and 200π.Assuming the –6dB isobar to be the shadow boundary, the authors found an almost linear proportionality between the relative shadow range and the ka parameter. The proportionality coefficient was determined and hence a basic formula was given which connects the shadow range, the sphere radius with the wavelength. It can be useful in many ultrasonic problems.